PENGARUH PEMBERIAN DANA PENGEMBANGAN, BUSINESS COACHING, DAN MARKETING TERHADAP KEBERHASILAN USAHA PESERTA P2MW - Maulidiananda, Widya; Indarti, Nunuk; Sangadji, Etta Mamang (E-Prosiding Seminar Nasional Manajemen dan Akuntansi STIE Semarang (SNMAS), 2024)
The Independent Learning-Independent Campus (MBKM) policy through the Student Entrepreneurship Development Program (P2MW) was launched by the Ministry of Education, Culture, Research, and Technology to prepare students to face the world of work and strengthen the entrepreneurial ecosystem by funding student proposals at Universitas PGRI Wiranegara. With this funding and mentoring, it is hoped that the success of student businesses will increase and develop innovative, impactful, and sustainable characters. The purpose of this study was to determine the effect of providing development funds, business coaching, and marketing on business success. The research design used was causal and descriptive using quantitative methods; the instruments used were questionnaires given to 40 research samples. The analysis tests used were the classical assumption test and multiple linear regression analysis, followed by partial tests and simultaneous tests. The results of the study showed that there was a positive and significant influence, partially and simultaneously, between the provision of development funds, business coaching, and marketing on the success of the businesses of participants in the student entrepreneurship development program. With an R square value of 75.5% obtained, which had a simultaneous contribution to the success of the businesses of participants in the student entrepreneurship development program at Universitas PGRI Wiranegara. Meanwhile, 24.5% of business success is influenced by other variables that were not studied.